1984
DOI: 10.1073/pnas.81.22.6983
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequencing of the genes encoding the alpha and beta subunits of C-phycocyanin from the cyanobacterium Agmenellum quadruplicatum.

Abstract: Synthetic oligonucleotide probes were used to identify a cloned DNA fragment from the cyanobacterium Agmenellum quadruplicatum that contains the genes for the a and 13 subunits of C-phycocyanin. The coding region for the a- The derived amino acid sequences for both C-phycocyanin subunits were compared with other known C-phycocyanin sequences for homology. Homologies between the A. quadruplicatum a subunit and a subunits from other species were ==70%, as were homologies between the A. quadruplicatum 13 subunit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0
2

Year Published

1985
1985
1995
1995

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 35 publications
2
26
0
2
Order By: Relevance
“…In all cyanobacteria examined so far, the two subunits (a and 1B) of the major phycobiliproteins (AP, PC, and PE) are encoded by adjacent and cotranscribed genes (3,6,11,15,25,28,29,34). The genes specifying the linker polypeptides associated with either PC or AP are also found downstream from those coding for the PB with which they are associated.…”
Section: Discussionmentioning
confidence: 99%
“…In all cyanobacteria examined so far, the two subunits (a and 1B) of the major phycobiliproteins (AP, PC, and PE) are encoded by adjacent and cotranscribed genes (3,6,11,15,25,28,29,34). The genes specifying the linker polypeptides associated with either PC or AP are also found downstream from those coding for the PB with which they are associated.…”
Section: Discussionmentioning
confidence: 99%
“…Definition of the genetic lesions in these mutants may best be approached by DNA sequence analysis now that biliprotein genes from other cyanobacteria have been cloned and sequenced (6,7,20).…”
Section: Discussionmentioning
confidence: 99%
“…, Pilot and Fox (1984) Walsh et al (1980) Lau et al (1987a), Kalla et al (1988) Wilson et al (1991) Anderson and Grossman (1990) Apt and Grossman (1993b) Minami et al (1985) Offner and Pilot and Fox (1984), Glazer (1987) Freidenreich et al (1978), Williams and Glazer (1978), Glazer (1987) Lau et al (1987b), Kalla et al (1988) Wilson et al (1991 Anderson and Grossman (1990) Sidler et al (1990) Apt and Grossman (1993b) Minami et al (1985) Offner and Troxler (1983) Bryant et al (1985) Sidler et al (1981, Riimbeli et al (1987) Houmard et al (1986, Klotz et al (1986) Su et al (1992 Some cyanobacteria are found under several names depending on the publications and the data banks. For clarity, only the most common used strain designations (from the point of view of the authors) have been used for the table above.…”
mentioning
confidence: 99%